PENDIDIKAN AKHLAK REMAJA DALAM KELUARGA MUSLIM DI ERA INDUSTRI 4.0 - Partono, Partono (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
This Study aims to determine the determine the role of the old man and startegy improving education mannerst the teenager in a family muslim the of modern. And the concep to of education mannerst tenagger in a family muslim in the era of modern. The focus of a problem in this study about how the concep of the role of and strategy of educatin manners teenager in a family muslim in the era of modern in improving education manners on the teenagers. The kind of this study is the regearch kualitataif. This study is approch, approach kualitatif deskriptif. The sources of the data this study is the source of the data primary and data sources secondary. Methods used data is a observation, the interview, and the documentation. The results of research suggest that understanding of the paraents of education manners on the teenager is stil very less, an understanding of the old man about the science of religion islamic is still low so education manners teenagers domestic or family is vey limited and the concept of education family against the teen in education manners is giving knowledge to teenager individually at home.